2021
DOI: 10.3389/fphar.2021.692970
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Toxicity Induced by Chronic Vincristine Treatment

Abstract: Vincristine is an effective anticancer agent for treating leukemias, lymphomas, and other solid tumors. Vincristine’s better-known severe side effects include bone marrow depression, hyponatremia, peripheral neuropathy, and gastrointestinal distress. In recent years, cardiovascular damage also has been described during vincristine treatments. However, the vascular toxicity induced by vincristine is little studied. The aim of the present is to evaluate whether these alterations remain after the suspension of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 73 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…Vinblastine and vincristine are effective agents for treating various types of cancers, including leukemias, lymphomas, and other solid tumors 34 . To evaluate the effect of SA treatment on the production rate of these alkaloids, the amount of vinblastine and vincristine was measured at 1st, 2nd, 3rd and 7th days post-treatment by HPLC analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Vinblastine and vincristine are effective agents for treating various types of cancers, including leukemias, lymphomas, and other solid tumors 34 . To evaluate the effect of SA treatment on the production rate of these alkaloids, the amount of vinblastine and vincristine was measured at 1st, 2nd, 3rd and 7th days post-treatment by HPLC analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The main toxicities of procarbazine and lomustine (CCNU) are myelosuppression and gastrointestinal symptoms, while vincristine is neurotoxic and hepatotoxic, and has been reported to induce ischemic events due to its neurotoxicity ( 23 ). Additionally, chronic vincristine treatment may induce cardiovascular toxicity ( 5 ). TMZ is a type of oral alkylating agent with the most common side-effects being gastrointestinal and hematologic toxicity ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antineoplastic therapy, such as chemotherapy, is known to prolong the survival of cancer patients. However, it can also induce cardiotoxicity, including cardiomyopathy, arrhythmias and other types of cardiovascular disease (CVD) (5,6). CVD has become the second leading cause of death in patients with CNS tumors (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the vinca alkaloids vincristine and vinblastine, that block microtubule formation in mitotic spindle leading to the arrest of cell division of metaphase, may induce hypertension, angina, and ischemic heart disease [ 372 ]. Among the mechanisms proposed, Herradón and co-workers found that alterations of TNFα, eNOS and iNOS in cardiac tissue after chronic treatment with vincristine may be responsible for alterations of heart function; moreover, the increase in mitochondrial connexin 43 expression induced by vincristine suggests that this important cardioprotective regulator counteracts the detrimental increase in free radical to protect the heart tissue from apoptotic damage [ 372 , 373 ].…”
Section: Anticancer Therapies and Cardiotoxicity: A Role For Mitochon...mentioning
confidence: 99%